PERK Limits Drosophila Lifespan by Promoting Intestinal Stem Cell Proliferation in Response to ER Stress. - Wang, L.; Ryoo, H.D.; Qi, Y.; Jasper, H. (PLoS Genetics, 2015)
Intestinal homeostasis requires precise control of intestinal stem cell (ISC) proliferation. In Drosophila, this control declines with age largely due to chronic activation of stress signaling and associated chronic inflammatory conditions. An important contributor to this condition is the age-associated increase in endoplasmic reticulum (ER) stress. Here we show that the PKR-like ER kinase (PERK) integrates both cell-autonomous and non-autonomous ER stress stimuli to induce ISC proliferation. In addition to responding to cell-intrinsic ER stress, PERK is also specifically activated in ISCs by JAK/Stat signaling in response to ER stress in neighboring cells. The activation of PERK is required for homeostatic regeneration, as well as for acute regenerative responses, yet the chronic engagement of this response becomes deleterious in aging flies. Accordingly, knocking down PERK in ISCs is sufficient to promote intestinal homeostasis and extend lifespan. Our studies highlight the significance of the PERK branch of the unfolded protein response of the ER (UPRER) in intestinal homeostasis and provide a viable strategy to improve organismal health- and lifespan.